14. yüzyılda musiki tasavvuru: Hasan Kâşânî’nin “kenzü’t-tuhaf” adlı eseri - (:unkn) unknown (My University, 2011)
14. yüzyılda, İslam dünyasında musiki tasavvuru, kaynakların ve araştırmaların yetersizliğigibi sebeplerle, hakkında çok fazla çalışılma yapılmamış bir konudur. Ancak araştırmalara görebu dönem, Safiyüddin Urmevî’nin sisteminin tartışılıp şerh edildiği, Merâgî gibi önemli bir musiki âliminin gelişine zemin hazırlayan önemli bir dönemdir. Ayrıca musiki perdelerinin isimleri, ilkdefa bu dönemde ortaya çıkmıştır. Bu makalede, 14. yüzyılda Hasan Kâşânî tarafından yazılmışKenzü’t-Tuhaf isimli Farsça musiki risalesi üzerinden, dönemin musiki anlayışı, nazariyatı ve sazları konusu tartışılmaktadır.

Our knowledge of the musical vision of the fourteenth century in the Islamic world is very insufficient because of the lack of sources and relevant research. However, this century is a very important period in which the musical system of Safiyyüddîn was discussed and annotated, and so it prepared the ground for the coming of an important scholar such as Meragî. In addition, the names of the tones (desâtîn) appear for the first time in a source. In this article, I have analyzed the understanding of music, music theory, and musical instruments of the fourteenth century, deriving information from a Persian treatise named Kenzü’t-Tuhaf written by Hasan Kâşânî in the fourteenth century.
Perception of music in the fourteenth century: Hasan Kâşânî’s “kenzu’t-tuhaf
Keywords: Tarih; Din Bilimi